(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2018)
This article describes the process of designing and implementing a unique four-week lesson plan that enables the students to put into practice all the knowledge acquired during the academic year, by using a series of cultural materials like videos, readings, etc. This experience takes place every year at the University of Toulouse Jean Jaurès, within the framework of Catalan language classes aimed at specialists from other disciplines (LANSAD). The starting point is Sant Jordi’s Day, a representative Catalan tradition and a culture date, in which literary works play an eminent role. The importance of books provides a unique opportunity to introduce to our various levels of LANSAD the work and the figure of different current Catalan writers, preferably polyhedral and complex authors, who represent several literary genres. The choice of an author still alive allows us to emphasize the contemporaneous nature of literature to our students. This lesson plan is implemented taking into account previous student knowledge and upholding the specific pedagogical objectives of each group. At the end of the unit, students will have explored the biography and works of the selected writer. In addition, a final meeting with the author will give learners the opportunity to exchange with him or her all those hypotheses and questions that arose during the lessons. Key words: didactics, Catalan, culture, language, literature.